Strategi Komunikasi Keluarga Beda Budaya dalam Mendidik Anak - zamri (At-Tabayyuun: Journal Islamic Studies, 2019)
Different Family Culture communication strategy in educating Children aims to understand and examine what factors that hampered communication interactions in different family culture in educating children and to understand and examine what factors that become advocates in different cultural communication interfacing family. Thus the construction of a culture that is owned by someone that, retrieved from an infant up to the liang lahat, and this greatly influences the way of thinking, behavingperson concerned in interact and communicate with people of different cultures. Even the collision of cultural interactions between often we experience everyday, culture includes communications involving participants representing private communication, interpersonal, and groups, with stress on the difference of cultural backgrounds that affect communication behavior in the hope it can serve as inputs in the intercultural communication in the study and provide a contribution on aspects of culture itself.